(untitled) (Modern education and development, 2024)
This article explores the communicative role of silence in human interaction. As the absence of speech, silence conveys a range of meanings and can sometimes be more powerful than words. The study employs a dual-method approach, combining a literature review and a survey conducted among university students. Key functions of silence, such as emphasizing points, reflecting, expressing agreement or disagreement, and fostering comfort or discomfort, are analyzed. The paper also highlights cultural differences in the interpretation of silence and its significance in communication across various contexts.